Efektivitas Terapi Hipnosis Lima Jari Terhadap Penurunan Kecemasan Pada Penderita Hipertensi Di UPT Puskesmas Helvetia Medan 2024 - Suarni, Leny Suarni; Wahyuni, Sri; -, Suniati (Jurnal Maternitas Kebidanan, 2024)
Hypertension is a vascular disorder that impedes the blood’s oxygen supply to body tissues, posing a serious health risk and a leading cause of premature mortality worldwide. Those affected by hypertension often struggle with anxiety, fear, despair, and sleep disturbances, which can further elevate blood pressure. One therapeutic approach for alleviating anxiety is the five-finger hypnosis technique. This study investigates the effectiveness of five-finger hypnosis therapy in reducing anxiety among hypertension patients at the UPT Helvetia Health Center Medan. Conducted as a quasi-experimental study using a one-group pretest-posttest design, the research sampled 33 respondents through purposive sampling. Data collection utilized the Hamilton Anxiety Rating Scale (HRSA) questionnaire, and results were analyzed with the Paired T-Test and Wilcoxon test. Findings showed a significant effect, with a p-value of 0.001, indicating that five-finger hypnosis therapy effectively reduces anxiety in hypertension patients at the Helvetia Health Center. It is anticipated that this research will encourage broader adoption of the five-finger hypnosis technique to manage anxiety more effectively.